Monitoring Export Vulnerability to Changes in Growth Rates of Major Global Markets - Hollweg, Claire H.; Lederman, Daniel; Reyes, José-Daniel (World Bank, Washington, DC, 2013)
Interest in assessing the impacts on developing countries of changes in major markets' economic performance has risen in tandem with global economic uncertainty over short- and medium-term growth prospects. This paper proposes a methodology to measure the vulnerability of a country's exports to fluctuations in the economic activity of foreign markets. Export vulnerability depends first on the overall level of export exposure, measured as the share of exports in gross domestic product, and second on the sensitivity of exports to fluctuations in foreign gross domestic product. The authors capture this sensitivity by estimating origin-destination specific elasticities of exports with respect to changes in foreign gross domestic product using a gravity model of trade. Furthermore, export vulnerability is computed separately for commodities and differentiated products. This methodology is applied to six developing countries, one from each World Bank region, selected to be otherwise similar yet differ in terms of the level of exposure to major global markets as well as the product composition of their export basket. Although the results suggest differences in elasticity estimates across regions as well as product categories, the principal source of international heterogeneity in export vulnerability results from differences in export exposure to global markets. This result calls for developing countries to diversify their export markets rather than shielding themselves from international markets, which would actually raise economic risk and vulnerability.